2006
DOI: 10.1002/cncr.22094
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immunoglobulin VH gene mutation status and other prognostic factors on the incidence of major infections in patients with chronic lymphocytic leukemia

Abstract: BACKGROUND.Infections are a major factor in the clinical course of chronic lymphocytic leukemia (CLL) and account for 30% to 50% of all deaths. The pathogenesis of infections in CLL is related to hypo‐γ‐globulinemia, T‐cell immune dysfunction, and the immunosuppressive effect of treatment.METHODS.The authors retrospectively assessed the correlations between new prognostic markers and types of infections encountered, the time taken to develop these infections, and infection‐related mortality in 280 unselected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 37 publications
5
49
0
7
Order By: Relevance
“…Recent studies have reported on the potential association between high-risk prognostic markers (e.g., elevated thymidine kinase, CD38 + status, unmutated IgV H status, and presence of genomic abnormalities) and an increased risk of developing infectious complications in patients with CLL [11,15]. The utility of these biomarkers in clinical practice remains to be established.…”
Section: Patient Predisposition To Infectionsmentioning
confidence: 99%
“…Recent studies have reported on the potential association between high-risk prognostic markers (e.g., elevated thymidine kinase, CD38 + status, unmutated IgV H status, and presence of genomic abnormalities) and an increased risk of developing infectious complications in patients with CLL [11,15]. The utility of these biomarkers in clinical practice remains to be established.…”
Section: Patient Predisposition To Infectionsmentioning
confidence: 99%
“…13, 40 In a study of 231 patients, those with U-CLL had increased infectious morbidity and mortality and shorter time to first infection compared with those with M-CLL. 40 Another study of untreated patients showed that U-CLL tumors were correlated with shorter time to onset of recurrent infection.…”
mentioning
confidence: 99%
“…40 Another study of untreated patients showed that U-CLL tumors were correlated with shorter time to onset of recurrent infection. 13 However, U-CLL progress more rapidly, 3 and it remains difficult to exclude that the differences depend on different tumor load in the subsets.…”
mentioning
confidence: 99%
“…65,66 These percentages are probably higher in patients who are refractory to fludarabine and/or alemtuzumab, 15,29 precisely those patients who are referred for allo-HCT. This susceptibility is both disease and therapy-related and is secondary to multiple factors, including hypogammaglobulinemia, defective T and natural killer cell function, neutropenia, and deficient complement activity.…”
Section: High Infection Rates Resulting From Preexisting Immunosupprementioning
confidence: 99%